Właściwości układu oddechowego młodzieży warszawskiej a zanieczyszczenie środowiska - Dorota Strzyżewska (Studia Ecologiae et Bioethicae)
This work presents studies on secondary school children inhabiting two regions of Warsaw: Śródmieście (Central part) and Międzylesie (East part). These two locations significantly differ according to air pollution, which is much higher in Śródmieście than in Międzylesie. the sample consist of 219 boys and 225 girls aged 13-16 years. The main aim of this work concerns the evaluation of physical development (body height and weight, BMI and chest circumference, Marty index – chest circ./height) and respiratory parameters (VC, Ziemssen index – VC/height, MV, FEV1 RR, TV, IRV, ERV, Ap) of studied children depending on the place of residence. The data were presented in “z” scores and the difference was calculated using t-test for independent samples. The results show that there were not significant differences in body build as well as in most respiratory functions between children from the Central and East parts of Warsaw. The significant differences were found for IRV and Ap which were greater in children from Śródmieście and for TV and MV which were greater in girls from Międzylesie. The more detailed analysis of these studies, including data concerning living conditions of studied children and smoking habits within their families is under preparation.